The role of husband and wife in managing family finances from the perspective of maqashid sharia - Khuluq, Arif Husnul; Ashari, Winning Son; Haq, Yusdi (Asy-Syari’ah : Jurnal Hukum Islam, 2025)
Every married couple certainly wants harmony and happiness from their marriage. However, in reality, marriages often fail to realize these noble goals, and end in divorce. One of the most common causes of divorce is economic factors. The good role of husband and wife in managing family finances is expected to be part of the solution to these problems. Islam has noble goals in its legal regulations (maqashid sharia), including those related to marriage. This study was conducted with the aim of analyzing how good the role of husband and wife is in managing family finances from the perspective of maqashid sharia to realize the desired harmony and happiness. This research is a literature review, and uses library research as a data collection method, using maqashid sharia theory as the analytical tool. The results of the study show that in order for the goals of marriage to be realized, husband and wife need to play an equal role and synergize with each other in managing family finances, both during planning, implementation and evaluation. How big each role is in managing family finances can vary from one family to another, depending on each family's expertise in financial management, but still by considering the husband's status as head of the household. Allocation of funds should be based on needs, not just following desires. The more urgent the need, the more worthy it is to be the reason for allocating funds. Likewise, it is necessary to weigh the priority scale when there is a contradiction between needs according to the maqashid sharia, so that financial management is successful, a harmonious family is realized and happiness in the world and in the hereafter is achieved which is desired by every human being.